2015
DOI: 10.1111/1365-2664.12388
|View full text |Cite
|
Sign up to set email alerts
|

Thresholds in Caribbean coral reefs: implications for ecosystem‐based fishery management

Abstract: Summary1. Ecosystem-based management of coral reef fisheries aims to sustainably deliver a diverse portfolio of ecosystem services. This goal can be undermined if the ecosystem shifts into a different state, with altered ecosystem functions and benefits to people. If levels of drivers that cause transitions between states are identified, management measures could be aimed at maintaining drivers below these levels to avoid ecosystem shifts. 2. Analysing data from a large number of Caribbean coral reefs (N = 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
78
3
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(88 citation statements)
references
References 48 publications
(130 reference statements)
4
78
3
3
Order By: Relevance
“…Using these ecosystem features as a guide, practitioners can develop an integrated understanding of how drivers are likely to affect key features of the ecosystem and determine whether increasing or maintaining the type and intensity of pressures is likely to result in threshold behavior, and evaluate the relative impact of alternative management actions by being cognizant of which pressures drive ecosystem shifts, which are controllable, and how quickly a system may react to a change in drivers. For example, scientists and managers are currently developing ecosystem indicators for Caribbean coral reefs based on threshold responses of the ecosystem to overfishing (Karr et al, 2015). By analyzing monitoring data from a large number of sites that span a gradient of fishing intensity and reef condition, Karr et al found that lower fish biomass was correlated with several other ecosystem condition variables, including decreased fish diversity and coral cover, and increased macroalgal cover.…”
Section: Using Monitoring and Indicators To Measure Progressmentioning
confidence: 99%
See 2 more Smart Citations
“…Using these ecosystem features as a guide, practitioners can develop an integrated understanding of how drivers are likely to affect key features of the ecosystem and determine whether increasing or maintaining the type and intensity of pressures is likely to result in threshold behavior, and evaluate the relative impact of alternative management actions by being cognizant of which pressures drive ecosystem shifts, which are controllable, and how quickly a system may react to a change in drivers. For example, scientists and managers are currently developing ecosystem indicators for Caribbean coral reefs based on threshold responses of the ecosystem to overfishing (Karr et al, 2015). By analyzing monitoring data from a large number of sites that span a gradient of fishing intensity and reef condition, Karr et al found that lower fish biomass was correlated with several other ecosystem condition variables, including decreased fish diversity and coral cover, and increased macroalgal cover.…”
Section: Using Monitoring and Indicators To Measure Progressmentioning
confidence: 99%
“…When fish biomass fell below the first threshold (50% of mean unfished biomass) they observed decreased fish species richness and increased macroalgal cover. When fish biomass fell below the second threshold (30% of mean unfished biomass) additional changes were detected, including reduced coral cover and urchin and herbivorous fish abundance and higher ratios of macroalgae to coral (see Figure 3 in Karr et al, 2015), indicative of a phase shift to algal dominance. Importantly, fish biomass thresholds and indicators were robust across scales (i.e., similar patterns are seen at local and regional scales) and can be used in data-limited systems.…”
Section: Using Monitoring and Indicators To Measure Progressmentioning
confidence: 99%
See 1 more Smart Citation
“…Although precariousness has been suggested in the wider ecological literature Hodgson, McDonald & Hosken 2015), it has not been specifically measured for coral reefs. While the locations of unstable equilibria and thresholds have only been estimated for a very limited range of reefs, an interim approach might be to use the distance between a reef's current state and the 'tipping points' identified for some Indian Ocean and Caribbean reefs for average system state against fish biomass (McClanahan et al 2011;Karr et al 2015). One advantage is that precariousness does not require the user to undertake modelling themselves.…”
Section: ) Precariousnessmentioning
confidence: 99%
“…Therefore, there remains a need for studies to identify the proximate drivers of reef dynamics across a diversity of environments (Chollett et al 2012). Some of this can be achieved through globally-replicated experiments (Steneck, Arnold & Mumby 2014; and regional analyses of bivariate relationships (McClanahan et al 2011;Karr et al 2015), but it is critical that key processes are disaggregated and not lost as confounding effects in broad-scale studies ).…”
Section: Avenues For Future Researchmentioning
confidence: 99%